Promoting More Equitable Global Health Research, Education, and Community Partnerships: The Efforts of One US‑Based Academic Institution - Sarah Emoto; Laura Ferguson; Lourdes Baezconde-Garbanati; Howard Hu; Goleen Samari; Sofia Gruskin (Annals of Global Health)
Objectives: Equitable global health partnerships are recognized as critical for health equity; however, power imbalances and structural inequities continue to undermine these partnerships and ultimately their ability to achieve equitable health outcomes. As individuals within a US‑based academic institution engaged in global health partnerships during the current, complicated political moment, we recognize our responsibility to critically examine what it means for us to seek to engage equitably, both locally and globally. We therefore undertook an initiative to develop and adopt a set of principles to serve as internal guidance for how individuals within our institution engage in partnerships. We present our approach to promoting equity within our local and global research, education, and community partnerships, informed by existing literature, as an example of how academic institutions based in the Global North might seek to address power imbalances and to engage with others involved in similar efforts. Methods: We reviewed similar initiatives and existing principles. An internal, departmental committee coalesced around eight principles and drafted and iteratively refined their components. As part of ongoing, broader conversations with our partners, during this process, we engaged and sought the perspectives of our external partners, including from Brazil, India, and Kenya, to ensure the guidance was both informed by and resonated with their concerns about engaging with a US‑based institution. Findings: The principles of sustainability, mutual benefit and reciprocity, equitable governance, do no harm, locally identified priorities, compliance with ethical reviews and legal standards, information sharing, and accountability were elaborated and ultimately adopted by the full department faculty. Conclusions: Despite the best of intentions, we foresee challenges that may impact both implementation and outcomes. Continued reflection and dialogue with our partners and others engaged in similar initiatives is needed to address these challenges and the broader structural inequities embedded in global health.